1997
DOI: 10.1677/joe.0.1530061
|View full text |Cite
|
Sign up to set email alerts
|

Roles of GTP and phospholipase C in the potentiation of Ca2+-induced insulin secretion by glucose in rat pancreatic islets

Abstract: Glucose can augment insulin secretion independently of K+ channel closure, provided cytoplasmic free Ca2+ concentration is elevated. A role for phospholipase C (PLC) in this phenomenon has been both claimed and refuted. Recently, we have shown a role for GTP in the secretory effect of glucose as well as in glucose-induced PLC activation, using islets pre-treated with GTP synthesis inhibitors such as mycophenolic acid (MPA). Therefore, in the current studies, we examined first, whether glucose augments Ca(2+)-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Several pieces of evidence from two laboratories (58,66,74) have established that the amplifying action of glucose does not involve the phospholipase C-protein kinase C pathway in the mouse. Discordant conclusions have been reached for the rat ␤-cell (65,74,75), but the most thorough study of the question also concluded that phospholipase C activation cannot be the major cause of glucose amplification of insulin secretion (75).…”
Section: The Amplifying Pathway Of Glucose-induced Insulin Secretionmentioning
confidence: 99%
“…Several pieces of evidence from two laboratories (58,66,74) have established that the amplifying action of glucose does not involve the phospholipase C-protein kinase C pathway in the mouse. Discordant conclusions have been reached for the rat ␤-cell (65,74,75), but the most thorough study of the question also concluded that phospholipase C activation cannot be the major cause of glucose amplification of insulin secretion (75).…”
Section: The Amplifying Pathway Of Glucose-induced Insulin Secretionmentioning
confidence: 99%
“…Glucose is the major stimulant for insulin secretion; however, the exact mechanism by which glucose induces insulin secretion still remains to be defined (Vadakekalam et al, 1997). Glucose can augment insulin secretion independently of K + channel closure, provided that the cytoplasmic free Ca 2+ concentration is elevated (Gembal et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Glucose can augment insulin secretion independently of K + channel closure, provided that the cytoplasmic free Ca 2+ concentration is elevated (Gembal et al, 1992). A role for phospholipase C (PLC) in this phenomenon has been both claimed (Turk et al, 1993;Zawalich and Zawalich, 1997) and refuted (Gembal et al, 1993;Vadakekalam et al, 1997). Kelly et al (1994) suggested that the enhanced phosphoinositide (PI) response was partially Ca 2+ -dependent and might involve activation of distinct isozymes of PLC expressed in the islets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Receptors for a number of hormones and growth factors are situated in the plasma membrane of both endocrine and acinar cells. These receptors are known to be coupled with G protein, PLC and PKC [8][9][10]. Recently, we demonstrated the site-specific distribution of PLC in rat pancreas by immunohistochemistry and Western blot analysis [11].…”
Section: Introductionmentioning
confidence: 99%